A policymaker’s guide to increasing youth engagement in aquaculture in Nigeria - Nigussie, Likimyelesh; Minh, Thai Thi; Senaratna Sellamuttu, Sonali (WorldFish, 2022)
Supporting young people to enter food value chains can help reduce high levels of youth unemployment across sub-Saharan Africa. The International Water Management Institute (IWMI) and WorldFish conducted a study to understand the drivers of, and hindrances to, youth entry into aquaculture value chains in Nigeria to support development of youth-inclusive policy for rural areas.